Self Regulation through Art and Chocolate - Lydia Royeen (Scholarworks @ WMU, 2015)
Josh Banks provided the cover art for the spring 2015 issue of The Open Journal of Occupational Therapy. The cover art is titled "Birthday Party" because the piece resembles images involved in a birthday party: multicolored balloons, napkins, cakes, and icing. Josh created the piece using oil crayons on watercolor paper. Josh is sensory seeking and has difficulty using various types of materials, which include crayons, street chalk, and markers. After much experimentation, Josh is able to use nibs, a type of marker that does not have a cap. Josh is able to sit for 5-10 minute periods and participate in his artistic endeavors. His normally bright and charming demeanor suddenly turns to one of concentration and focus on his work. He uses short, intense strokes in his artwork. Vicki, his mother, has noted seasonal undertones in some of Josh's artwork and has named his pieces of art according to the season